CONTENT ANALYSIS AND SOCIAL NETWORK ANALYSIS: A TWO-PHASE METHODOLOGY IN OBTAINING FUNDAMENTAL CONCEPTS OF COOPETITION - Suzanna Lamria Siregar; Giovanni Battista Dagnino; Francesco Garraffo (Universitas Gunadarma, 2011)
This study introduces a two-phase methodology in obtaining fundamental conceptsfrom literature. Content analysis performed in the first phase leads to the mostfrequent concepts scholars used in scrutinizing a theme. Social network analysis in thesecond phase results a network of the relationships between concepts and examinesthe importance of every concept in the network. To elucidate the advantage of themethodology, the study applies the methodology on Coopetition – to cooperate andcompete simultaneously – literature. Ten most frequent concepts occur in thecoopetition literature are: Competition, Cooperation, Coopetition, Knowledge,Market, Network, Relationships, Resources, Strategy and Value. Under the socialnetwork analysis terms, the importance of every concept in the network is denoted indegree, closeness and betweenness centrality measures. Ranging from the mostimportant concepts to the least are Relationships, Strategy, Resources, Competition,Cooperation, Coopetition, Market, Network, Value and Knowledge